Impaired respiratory burst contributes to infections in PKC-deficient patients - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (ROCKEFELLER UNIV PRESS, 2021)
Patients with autosomal recessive protein kinase C delta (PKC delta) deficiency suffer from childhood-onset autoimmunity, including systemic lupus erythematosus. They also suffer from recurrent infections that overlap with those seen in patients with chronic granulomatous disease (CGD), a disease caused by defects of the phagocyte NADPH oxidase and a lack of reactive oxygen species (ROS) production. We studied an international cohort of 17 PKC delta-deficient patients and found that their EBV-B cells and monocyte-derived phagocytes produced only small amounts of ROS and did not phosphorylate p40(phox) normally after PMA or opsonized Staphylococcus aureus stimulation. Moreover, the patients' circulating phagocytes displayed abnormally low levels of ROS production and markedly reduced neutrophil extracellular trap formation, altogether suggesting a role for PKC delta in activation of the NADPH oxidase complex. Our findings thus show that patients with PKC delta deficiency have impaired NADPH oxidase activity in various myeloid subsets, which may contribute to their CGD-like infectious phenotype.
Keywords: PROTEIN-KINASE-C; CHRONIC GRANULOMATOUS-DISEASE; SYSTEMIC-LUPUS-ERYTHEMATOSUS; NADPH OXIDASE; LYMPHOPROLIFERATIVE SYNDROME; P47(PHOX) PHOSPHORYLATION; TYROSINE PHOSPHORYLATION; CRYSTAL-STRUCTURE; CELL-SURVIVAL; THREONINE 154